PENYULUHAN PENINGKATAN KUALITAS PELAYANAN KESEHATAN PENGGUNA BPJS RAWAT INAP DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Ribka Flora Panjaitan; Diana Sinulingga (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
This study aims to determine and describe the quality of BPJS Inpatient Health Services at Grandmed Lubuk Pakam Hospital, Deli Serdang Regency, seen from the theory of service quality standards according to Groonros (in Tjiptono 2011), namely professionalism and skills (professionalism and expertise), attitudes and behavior. and Behavior), Accessibility and flexibility (Ease of achievement and adjustment of services), Realibility and trustworthiness (reliability and trust), Recovery (Control of situations and problem solving), Reputation and credibility (good name and can be trusted). The research method used is descriptive qualitative. There are 22 informants, namely patients or patients' families who receive services, the Head of Medical Services as the one who knows all processes and conditions of service by employees at the service counter, one of the staff at the BPJS health service counter at Grandmed Lubuk Pakam Hospital, Deli Serdang Regency The data source used is primary data obtained directly from informants while secondary data comes from existing data at Grandmed Lubuk Pakam Hospital, Deli Serdang Regency, documents relating to the problem to be studied. The results showed that the quality of BPJS Kesehatan services in Grandmed Lubuk Pakam, Deli Serdang Regency has generally been running well, although there are still some things that need to be improved, such as the unfriendly attitude of young medical officers and new administrative officers, reliability and trust in administrative officers and medical officers is still not maximal, it still needs to be improved.